Assessment of Soil Damage for Biomass Production in Slope Area Used as Agricultural Land in Tanggetada District, Kolaka Regency - La Mpia; Musadia Afa; Murni Handayani; Juniaty Arruan Bulawan (Agrotech Journal, 2022)
This study aimed to assess the soil degradation level for biomass production in sloping areas used as agricultural land. This research was conducted in Tanggetada District, Kolaka Regency. This research was conducted using a field survey method with a slope class approach which is used as agricultural land with a slope of 8-15%, 15-25%, 25-45%, and 45%. The results of the study show that the status of soil damage in sloped areas used as agricultural land in Tanggetada District, Kolaka Regency, for slope classes 8-15%, 15-25%, and 25-45% included in the lightly damaged category while slope classes 45% included in the moderately damaged category. The limiting factors for soil damage status at this location are surface rock, microbial count, bulk density, permeability, and redox